Decagram Synthesis of Dimethyl 1,4-Cubanedicarboxylate Using Continuous-Flow Photochemistry - Collin, Diego E.; Jackman, Edward H.; Jouandon, Nicolas; Sun, Wei; Light, Mark E.; Harrowven, David C.; Linclau, Bruno (Synthesis, 2020)
The highly strained cubane system is of great interest as a scaffold and rigid linker in both pharmaceutical and materials chemistry. A straightforward approach is reported for the scale-up of a [2+2] photocycloaddition step using convenient home-made flow photoreactors to access dimethyl 1,4-cubanedicarboxylate on decagram-scale in 33–40% yield over 8 steps. The process is demonstrated on 3.4 g·h–1 input with 30 minutes residence time, enabling to reduce the process time and to avoid the use of batch photoreactors. Completion of the characterisation of the photocycloadduct and its hydrates is reported.
Keywords: cubanes; continuous-flow; photochemistry; photocycloaddition; upscaling